Linguistic Markers of Emotions and Coping Stages in Narratives of Cancer Survivors - Su Hie, Ting; Faynella, Freddy (UNIMAS Publisher, 2025)
Linguistic markers in emotional disclosures have not been investigated to identify the stage of emotional adjustment to cancer. The study examined linguistic markers of emotions and coping stages in written narratives of cancer survivors. Using the Linguistic Inquiry and Word Count (LIWC) framework, 20 narratives with 18,287 words written by cancer survivors collected from five cancer organisation websites, blogs and online magazines were analysed. The 50 most frequently used words in the cancer narratives appeared 1,153 times because some words were repeatedly used. There were more negative emotional processes (39.20%) than positive emotional processes (18.73%) or cognitive processes (21.16%). Most of the narratives contained words associated to denial, depression, and acceptance. Depression and acceptance were recurring in the cancer narratives. The depression stage was associated with negative emotions but the acceptance stage was associated with cognitive processes. The findings suggest that the decline in emotional words co-occurs with an increase in cognitive words from depression to acceptance, suggesting that cognitive mechanisms are utilised to cope with cancer.